2021
DOI: 10.1093/nar/gkab549
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial analysis of translation dynamics reveals eIF2 dependence of translation initiation at near-cognate codons

Abstract: Although ribosome-profiling and translation initiation sequencing (TI-seq) analyses have identified many noncanonical initiation codons, the precise detection of translation initiation sites (TISs) remains a challenge, mainly because of experimental artifacts of such analyses. Here, we describe a new method, TISCA (TIS detection by translation Complex Analysis), for the accurate identification of TISs. TISCA proved to be more reliable for TIS detection compared with existing tools, and it identified a substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…In yeast and human cells it was demonstrated that in ribosome profiling (Ribo-seq) the length of a ribosome footprint informs about the conformation of the ribosome during its ratcheting motion on mRNA (21). To find further evidence that arsenite stalled ribosomes in the CDS, we therefore first turned to a published Ribo-seq dataset investigating arsenite-induced translational arrest in human HEK293 cells (22). Indeed, we observed a strong 2.5 fold shift from 21 nucleotide reads (pre-translocation) to 28 nucleotide reads (post-translocation) upon arsenite treatment in the published Ribo-seq data (two-sided Kolmogorov-Smirnov test p<2E-16, Figure S3A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In yeast and human cells it was demonstrated that in ribosome profiling (Ribo-seq) the length of a ribosome footprint informs about the conformation of the ribosome during its ratcheting motion on mRNA (21). To find further evidence that arsenite stalled ribosomes in the CDS, we therefore first turned to a published Ribo-seq dataset investigating arsenite-induced translational arrest in human HEK293 cells (22). Indeed, we observed a strong 2.5 fold shift from 21 nucleotide reads (pre-translocation) to 28 nucleotide reads (post-translocation) upon arsenite treatment in the published Ribo-seq data (two-sided Kolmogorov-Smirnov test p<2E-16, Figure S3A).…”
Section: Resultsmentioning
confidence: 99%
“…In order to validate the observations we had made for protein coding transcripts, where certain groups of mRNA increased their protein occupancy during arsenite stress, we cross-referenced them with published data from different cell lines. Therefore, we first asked if stalling ribosomes might be the cause for this increased occupancy and re-analyzed Ribo-seq data from arsenite-treated HEK293 cells (22). In this dataset, translation efficiencies of iPO mRNAs decreased strongly upon arsenite (p=2.7E-7, two-sided Kolmogorov-Smirnoff test, Figure S5A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initiation of translation in mammals is no longer thought to be as specific as it once was. Use of non-AUG codons under conditions in which eIF2α is active is now well documented [28, 39] ( Fig. 9A ).…”
Section: Resultsmentioning
confidence: 99%